Przesłanki udzielania pomocy publicznej na cele związane z ochroną środowiska - Bartniczak, Bartosz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The question of granting state aid in environment protection is relatively new. These problems in European law were regulated only in the 70's of the XX century. The aim of this article is to show the circumstances of granting state aid in environment protection. They are divided to ecological, economic, social and political and they show why the state should help entrepreneurs in environment protection. The article also shows where this aid is particularly important. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 13-21